2019
DOI: 10.1002/solr.201900041
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electronic Properties of SnO2 Quantum Dots via Aluminum Addition for High‐Efficiency Perovskite Solar Cells

Abstract: Owing to its splendid electrical and optical properties, tin oxide (SnO2) has been proven to be an effective electron transport layer (ETL) material for high‐efficiency perovskite solar cells (PSCs). However, the surface coverage, conductivity, and energy loss at the SnO2/perovskite interface still have room for improvement. Herein, a facile method by mixing a SnO2 QD solution with an aluminum (Al) chloride precursor solution at room temperature to achieve the addition of Al into the SnO2 QD (Al: SnO2) precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 41 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Among the aforementioned strategies, element doping is the simplest and most effective method for adjusting the energy band position and carrier concentration . Several researchers reported different elements doping, such as Li, Mg, Nb, and Cl, to improve electron transport performance.…”
Section: Introductionmentioning
confidence: 99%
“…Among the aforementioned strategies, element doping is the simplest and most effective method for adjusting the energy band position and carrier concentration . Several researchers reported different elements doping, such as Li, Mg, Nb, and Cl, to improve electron transport performance.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a magnificent energy conversion from solar power to electricity, photovoltaic (PV) devices exhibit their enormous potential in this application . Thereinto, halide perovskite solar cells (HPSCs), as a representative of the third‐generation cells, are very promising technology, due to their amazing optoelectronic features, as well as low cost and facile manufacturing . Since the first reported power conversion efficiency (PCE) of 3.8% by Miyasaka and coworkers in 2009, the record PCE of organic–inorganic hybrid HPSCs has rapidly surged to 24.2% up to now, making it a viable competitor to Si/InP‐based solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 60 ] b) Liu et al did the EDX mapping for KCl passivated SnO x layer and the uniform distribution of K, Cl, Sn, and O was observed which is similar to what we have observed in this study with Sn, O, Cs, and I, as shown in Figure S5, Supporting Information, and c) Al‐doped SnO x ESL‐based PSC was studied by Wang et al and the EDX mapping confirmed the uniform distribution of Al as similar to our results. [ 29,61 ] In Figure S5e, Supporting Information, the EDX spectrum quantifies the elemental percentage of iodine which is almost double the Cs content, which reveals that the more electronegative iodine was present on the surface of the films and it may act as a surface passivation between the interface. Recently, Jiang et al reported that phenethylammonium iodide post‐treatment passivation strategy reduces the iodine vacancy and improves the PCE to 23.3% with V oc of 1.18 V compared with pristine with V oc of 1.12 V. [ 20 ] This clearly indicates that the excess iodine on the doped SnO x surface may control the iodine vacancies and reduce the interface recombination at the perovskite/CsI–SnO x interface than pristine SnO x .…”
Section: Resultsmentioning
confidence: 99%
“…to control the mobility, band edge tuning, and defect density of the bulk SnO x . [ 27–36 ] 2) surface passivation strategy is used to suppress the dangling bonds (undercoordinated sites) in SnO x surface using electropositive and electronegative molecules which helps in fine‐tuning the surface work function and defect density with respect to the top perovskite layer and thereby improving the charge extraction process. Electropositive molecules like phosphoric acid, acetic acid, and electronegative molecules like (NH 4 ) 2 S are used to control the corresponding defects on the SnO x surface.…”
Section: Introductionmentioning
confidence: 99%